Energy Generation from Static Water Head Developed By Forward Osmosis - A. Al-Hemiri, Adel; A. Mohammed, Ghazwan; F. Naser, Ghazi (Iraqi Journal of Chemical and Petroleum Engineering, 2011)
In this work, the possibility of utilizing osmosis phenomenon to produce energy as a type of the renewable energy using Thin Film Composite Ultra Low Pressure membrane TFC-ULP was studied. Where by forward osmosis water passes through the membrane toward the concentrated brine solution, this will lead to raise the head of the high brine solution. This developed static head may be used to produce energy. The aim of the present work is to study the static head developed and the flux on the high brine water solution side when using forward and reverse osmosis membranes for an initial concentration range from 35-300 g/l for each type of membrane used at room temperature and pressure conditions, and finally calculating the maximum possible power generated from developed static head.